The philosophical journey to Being and Nothingness: how many “phenomenologies” does it take to make a phenomenological ontology? - Yazbek, Andre Constantino (Argumentos - Revista de Filosofia, 2025)
This paper intends to recover the “phenomenological” basis of Sartre’s trajectory since his very first reception of Edmund Husserl’s and Martin Heidegger’s philosophies until the moment in which the main synthesis of his existentialism is published, entitled Being and Nothingness (1943). In this sense, the paper situates the status of Husserl’s and Heidegger’s phenomenologies for Sartrean thought, as well as the originality of Being and Nothingness, which is also influenced by a very particular interpretation of Hegelian negation.